Statistically Optimized Polymeric Buccal Films of Eletriptan Hydrobromide and Itopride Hydrochloride: An In Vivo Pharmacokinetic Study - Awaji Y. Safhi; Waqar Siddique; Muhammad Zaman; Rai Muhammad Sarfraz; Muhammad Shafeeq Ur Rahman; Asif Mahmood; Ahmad Salawi; Fahad Y. Sabei; Abdullah Alsalhi; Khalid Zoghebi (MDPI AG, 2023)
A migraine is a condition of severe headaches, causing a disturbance in the daily life of the patient. The current studies were designed to develop immediate-release polymeric buccal films of Eletriptan Hydrobromide (EHBR) and Itopride Hydrochloride (ITHC) to improve their bioavailability and, hence, improve compliance with the patients of migraines and its associated symptoms. The prepared films were evaluated for various in vitro parameters, including surface morphology, mechanical strength, disintegration test (DT), total dissolving time (TDT), drug release and drug permeation, etc., and in vivo pharmacokinetic parameters, such as area under curve (AUC), mean residence time (MRT), half-life (t1/2), time to reach maximum concentration (Tmax), and time to reach maximum concentration (Cmax). The outcomes have indicated the successful preparation of the films, as SEM has confirmed the smooth surface and uniform distribution of drugs throughout the polymer matrix. The films were found to be mechanically stable as indicated by folding endurance studies. Furthermore, the optimized formulations showed a DT of 13 ± 1 s and TDT of 42.6 ± 0.75 s, indicating prompt disintegration as well as the dissolution of the films. Albino rabbits were used for in vivo pharmacokinetics, and the outcomes were evident of improved pharmacokinetics. The drug was found to rapidly permeate across the buccal mucosa, leading to increased bioavailability of the drug: Cmax of 130 and 119 ng/mL of ITHC and EHBR, respectively, as compared to 96 (ITHC) and 90 ng/mL (EHBR) of oral solution. The conclusion can be drawn that possible reasons for the enhanced bioavailability could be the increased surface area in the form of buccal films, its rapid disintegration, and faster dissolution, which led toward the rapid absorption of the drug into the blood stream.